Invisible atrocities : the aesthetic biases of international criminal justice - DeFalco, Randle C., 1982- (Cambridge : Cambridge University Press, 2022)
International criminal justice is, at its core, an anti-atrocity project. Yet just what an 'atrocity' is remains undefined and undertheorized. This book examines how associations between atrocity commission and the production of horrific spectacles shape the processes through which international crimes are identified and conceptualized, leading to the foregrounding of certain forms of mass violence and the backgrounding or complete invisibilization of others. In doing so, it identifies various, seemingly banal ways through which international crimes may be committed and demonstrates how the criminality of such forms of violence and abuse tends to be obfuscated. This book suggests that the failure to address these 'invisible atrocities' represents a major flaw in the current international criminal justice system, one that produces a host of problematic repercussions and undermines the legal legitimacy of international criminal law itself.
Introduction : visible and invisible atrocity crimes -- The atrocity aesthetic : international crimes as horrific spectacles -- Maintaining invisibility : aesthetic perception and the recognition of international crimes -- Unspectacular atrocities and international criminal law -- Visible and invisible international crimes : Cambodia and beyond introduction -- The costs of invisibility : an incomplete list introduction -- Aesthetic bias and legal legitimacy : an interactional assessment -- Conclusion : addressing the many forms of atrocity crimes.
Title from publisher's bibliographic system (viewed on 11 Mar 2022).
Keywords: Atrocities -- Law and legislation; International criminal law; World War, 1914-1918 -- Atrocities; Criminal justice, Administration of -- International cooperation